Desenvolvimento de um modelo matemático para a transferência de calor para tubos de aço submetidos ao processo de têmpera por anéis - Daniela Fatima Gomes (2017)
The quenching process is one of the most important steps in steel pipe production and has a significant impact on the quality of the product. Several parameters affect the performance of the process, including initial temperature of the tube and its speeds. Mathematical models have been developed to simulate the heat transfer in this process and to improve the conditions being adopted the conduct the cooling of the tubes. In the present work, a mathematical model was developed to simulate the quenching in a system of cooling rings with water sprays. Two-dimensional and three-dimensional models were developed. The verification of the two-dimensional model was performed by comparison with a known analytical solution problem and the results obtained by the three-dimensional model were compared with the solution calculated by the ANSYS software. In the verification stage, it was demonstrated that the program developed for the numerical solution of the conservation energy equation was correct.The model was validated by comparison with the results of an experiment carried out in an industrial scale Several heat transfer simulations have been carried out, comparing different approaches in the modeling. The results showed that the space between the cooling rings can lead to a non-uniform temperature profile, the heat transfer along the axial direction should not be ignored in situations where there are spaces between the cooling rings. An increase in the speed of rotation of the tube leads to a more uniform temperature distribution in the angular direction